Metal resin bond grinding block for ceramic slab rough grinding process and preparation method thereof
Patent Information
- Application Number
- CN202311319714.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-10-11
AI Technical Summary
[0006]然而,这种热压树脂磨块在粗磨抛光过程中寿命较短,磨块较脆,磨块周缘容易烂齿,掉渣,导致陶瓷面板产生磨花
[0030] (1) The grinding blocks used in the rough grinding process of this invention are made by combining hot-pressed strip metal with cast liquid resin to obtain metal-resin combined grinding blocks. The metal-resin combined modules replace the existing hot-pressed resin grinding blocks. On the one hand, the sharpness and service life of the grinding blocks can be improved. On the other hand, the polishing effect can be improved. The resulting ceramic slabs have no scratches on the surface, high flatness of the brick surface, and no bending of light under fluorescent lamps.
Smart Images

Figure CN117444869B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic processing, and in particular to a metal-resin bonded grinding block and its preparation method for the rough grinding process of large ceramic slabs. Background Technology
[0002] Large ceramic slabs are made from various inorganic non-metallic materials such as clay and minerals through a high-temperature firing process at 1200℃. Compared to other ceramic tile products, large ceramic slabs are characterized by their large size, high hardness, stable performance, safety and durability, environmental friendliness and health benefits, and strong decorative appeal. They are mainly used for wall and floor decoration in architectural spaces, as well as for furniture decoration such as wardrobe panels, cabinet panels, and door panels.
[0003] However, due to its large production size (such as 3600mm×1600mm×15.5mm) and poor surface flatness, water ripples occur during polishing, reducing the customer's yield.
[0004] Before being finished, ceramic slabs require polishing, which includes coarse grinding, medium grinding, and fine grinding. Coarse grinding mainly removes surface imperfections and reshapes the slab, maintaining its approximate geometry and roughness. Coarse grinding improves polishing efficiency and reduces wear on the grinding tools during subsequent polishing processes. Medium grinding follows coarse grinding and is used to further smooth out any uneven areas on the surface of the ceramic slab, facilitating subsequent polishing through fine grinding.
[0005] In the current polishing process of large ceramic slabs, the rough grinding step uses hot-pressed resin grinding blocks, the structure of which is as follows: Figure 1 As shown, its formula is mainly prepared by hot pressing of the following components in parts by weight: 30-40 parts powdered phenolic resin, 5-12 parts zinc oxide, 15-25 parts green silica, 5-10 parts alumina, 2-5 parts glass fiber powder, 2-5 parts calcium carbonate, and 8-15 parts diamond. Depending on the polishing requirements of the coarse grinding, the diamond particle size in the coarse grinding block is 0.08-0.16 mm, and the green silica particle size is 120-300 mesh.
[0006] However, these hot-pressed resin abrasive blocks have a short lifespan during rough grinding and polishing. They are brittle, and the edges are prone to chipping and splintering, resulting in scratches on the ceramic panel. Furthermore, the flatness of the large ceramic slab cannot be guaranteed.
[0007] Therefore, this patent mainly focuses on developing a grinding block for the coarse grinding process of ceramic slabs, which can improve the sharpness and service life of the grinding block while ensuring the flatness of the surface of the processed ceramic slab. Summary of the Invention
[0008] In order to overcome the shortcomings of the prior art, one of the objectives of the present invention is to provide a metal-resin bonded grinding block for the rough grinding process of ceramic slabs.
[0009] The second objective of this invention is to provide a method for preparing a metal-resin bonded grinding block for the coarse grinding process of ceramic slabs.
[0010] One of the objectives of this invention is achieved by the following technical solution: a metal-resin bonded grinding block for the rough grinding process of ceramic slabs, the metal-resin bonded grinding block mainly consists of a corrugated metal part and a resin part poured around the metal part.
[0011] The metal part is prepared from the following components in parts by weight: 10-30 parts of foamed copper powder, 3-10 parts of foamed nickel powder, 5-15 parts of diamond, 20-40 parts of iron-copper alloy powder, 5-10 parts of phosphorus iron powder, 15-30 parts of carbonyl iron powder, and 1-5 parts of phosphorus powder.
[0012] The resin component is prepared from abrasive powder, unsaturated resin liquid, cobalt solution, methyl ethyl ketone peroxide, diluent, and coupling agent. The weight ratio of abrasive powder to unsaturated resin liquid is 1:(0.7-1.2). The amount of cobalt solution added is 1-2% of the weight of the unsaturated resin liquid, the amount of methyl ethyl ketone peroxide added is 2-4% of the weight of the unsaturated resin liquid, the amount of diluent added is 1-3% of the weight of the unsaturated resin liquid, and the amount of coupling agent added is 3-5% of the weight of the unsaturated resin liquid. The abrasive powder is prepared from the following components in parts by weight: 5-15 parts nylon powder, 5-15 parts zinc oxide, 5-15 parts copper foam powder, 10-20 parts black silicon carbide, 5-15 parts alumina, 1-5 parts calcium carbonate, and 5-15 parts diamond.
[0013] Furthermore, in the metal portion, the porosity of the foamed copper powder is 50-81%, and the average pore size is 0.2-4 mm.
[0014] Furthermore, in the metal portion, the porosity of the foamed nickel powder is 50-98%, and the average pore size is 0.1-2 mm.
[0015] Furthermore, in the metal portion, the diamond has a particle size of 0.08-0.16 mm, the iron-copper alloy powder has a particle size of 300-500 mesh, the phosphorus iron powder has a particle size of 800-1200 mesh, the carbonyl iron powder has a particle size of 300-500 mesh, and the phosphorus powder has a particle size of 300-500 mesh.
[0016] Furthermore, in the resin portion, the unsaturated resin liquid is selected from unsaturated polyester resin with grade 196 provided by Shin Yang Technology Co., Ltd.
[0017] Furthermore, in the resin portion, the diluent is selected from styrene, acetone, toluene, and butanol; the coupling agent is selected from silane coupling agents, titanate coupling agents, and aluminate coupling agents.
[0018] Furthermore, in the resin portion, the porosity of the foamed copper powder is 50-81%, and the average pore size is 0.2-4 mm.
[0019] Furthermore, in the resin portion, the nylon powder has a particle size of 300-500 mesh, the zinc oxide has a particle size of 300-500 mesh, the black silicon carbide has a particle size of 150-300 mesh, the alumina has a particle size of 300-500 mesh, the calcium carbonate has a particle size of 300-500 mesh, and the diamond has a particle size of 0.08-0.16 mm.
[0020] The second objective of this invention is achieved by the following technical solution: a method for preparing a metal-resin bonded grinding block for the rough grinding process of large ceramic slabs, comprising the following steps:
[0021] (1) Fabrication of the wavy metal parts
[0022] The metal part is prepared according to the following components by weight: 10-30 parts of foamed copper powder, 3-10 parts of foamed nickel powder, 5-15 parts of diamond, 20-40 parts of iron-copper alloy powder, 5-10 parts of phosphorus iron powder, 15-30 parts of carbonyl iron powder, and 1-5 parts of phosphorus powder. The above components, except for diamond, are mixed in a three-dimensional mixer for 30-50 minutes. Then, the amount of diamond in the formula and 1.5%-3% of liquid paraffin by weight of the powder are added, and the mixture is stirred again for 50-60 minutes. The mixed powder is poured into a graphite mold and pressed into shape using a hot press. After pressing, the surface is polished to remove burrs, resulting in a wavy metal part.
[0023] (2) Preparation of resin abrasive fluid
[0024] The abrasive powder is formulated according to the following components by weight: 5-15 parts nylon powder, 5-15 parts zinc oxide, 5-15 parts copper foam powder, 10-20 parts black silicon carbide, 5-15 parts alumina, 1-5 parts calcium carbonate, and 5-15 parts diamond. The abrasive powder is then passed through a 46# sieve and dried in an oven to remove moisture. The dried powder is then poured into a three-dimensional mixer for mixing for 1-2 hours. The resulting abrasive powder is then ready for use.
[0025] Add the prescribed amount of unsaturated resin liquid to the mixing tank, add diluent at a rate of 1-3% of the weight of the unsaturated resin liquid; then add the well-mixed abrasive powder, the weight ratio of the abrasive powder to the unsaturated resin liquid being 1:(0.7-1.2), and stir evenly; add silane coupling agent at a rate of 3-5% of the weight of the unsaturated resin liquid, and stir evenly; add cobalt water at a rate of 1-2% of the weight of the unsaturated resin liquid, and stir evenly; then add methyl ethyl ketone peroxide at a rate of 2-4% of the weight of the unsaturated resin liquid, and stir evenly to obtain the resin abrasive liquid; in step (2), the temperature of the oven is set to 55-65℃ and kept at that temperature for 0.5-1 hour;
[0026] (3) Combination of metal and resin parts
[0027] Place the mold into the mold slot, place the wavy metal part obtained in step (1) into the mold, pour the mixed resin abrasive liquid in step (2) into the mold, place the rubber pad on top of the mold so that the resin liquid and the rubber pad come into contact, then apply pressure to the rubber pad, turn on the ultrasonic device and the heating device, perform ultrasonic and hot-press curing, and take it out after complete curing. This is the metal resin bonded abrasive block for the rough grinding process of ceramic slabs.
[0028] Further, in step (1), the pressing conditions are as follows: the hot press is heated in stages from an initial temperature of 100℃ and 20KN to 750℃ and 100KN, and held for 2-4 minutes; in step (2), the oven temperature is set to 55-65℃ and held for 0.5-1 hour; in step (3), the ultrasonic frequency is set to 35-45kHz, the ultrasonic time is 0.5-1 hour, the heating temperature of the heating device is 50-80℃, and the pressing time is 1-3 hours.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0030] (1) The grinding blocks used in the rough grinding process of this invention are made by combining hot-pressed strip metal with cast liquid resin to obtain metal-resin combined grinding blocks. The metal-resin combined modules replace the existing hot-pressed resin grinding blocks. On the one hand, the sharpness and service life of the grinding blocks can be improved. On the other hand, the polishing effect can be improved. The resulting ceramic slabs have no scratches on the surface, high flatness of the brick surface, and no bending of light under fluorescent lamps.
[0031] Specifically, in terms of the shape and structure of the grinding block, a wavy metal strip is designed in the middle of the grinding block. On the one hand, the contact pressure between the wavy metal part and the surface of the ceramic slab to be processed is small, which avoids crushing the slab compared to a simple metal grinding block, and also ensures that the glaze layer on the upper surface of the ceramic slab is not damaged. On the other hand, unsaturated liquid resin is used instead of powdered resin in the resin part, which improves the hardness and toughness of the grinding block, plays an auxiliary grinding role in rough grinding, and improves the wear resistance of the grinding block.
[0032] In terms of the metal component formulation, the addition of foamed copper powder and foamed nickel powder, due to their three-dimensional porous structure and high porosity, allows the low-melting-point liquid resin to flow into the pores of the foamed copper and nickel powders under hot-pressing and molten conditions, forming a three-dimensional network structure that strengthens the matrix and effectively improves the toughness and wear resistance of the grinding block. In terms of the resin component formulation, the use of liquid resin instead of powdered resin further enhances the overall performance of the product by providing stronger adhesion between the liquid resin and the metal components.
[0033] (2) In the grinding block preparation method, the present invention pours liquid resin into the mold and introduces ultrasonic equipment during curing. The liquid resin formula contains foamed metal copper with large porosity. During the ultrasonic curing process, the high-speed micro-jet generated by ultrasonic cavitation enhances the stirring effect of the solution and strengthens the movement of powder in the resin liquid. Diamond and other fillers can more easily enter the pores, increase the bonding force, reduce the thickness of the dispersion layer and the concentration gradient, and ensure that the resin liquid and powder are mixed evenly.
[0034] (3) After the new metal resin combined grinding block is cured and molded, there is no need to arrange a separate process of pasting adhesive pads and / or Velcro. When the resin liquid is poured and cured, the grinding block and the adhesive pad adhere together, which simplifies the processing process and reduces the cost. Attached Figure Description
[0035] Figure 1 A schematic diagram of the structure of the hot-pressed resin grinding block (Comparative Example 13) in the existing rough grinding process of ceramic slabs;
[0036] Figure 2 This is a three-dimensional schematic diagram of a metal-resin bonded grinding block according to a preferred embodiment of the present invention;
[0037] Figure 3 This is a top view of a metal-resin bonded grinding block according to a preferred embodiment of the present invention;
[0038] In the diagram: 100, metal-resin bonded grinding block; 1, metal part; 2, resin part. Detailed Implementation
[0039] The present invention will now be further described in conjunction with the accompanying drawings and specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0040] In this invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used are commercially available or commonly used in the art. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art.
[0041] This invention provides a metal-resin bonded grinding block for the rough grinding process of large ceramic slabs, such as... Figure 2-3 As shown, the metal-resin bonded grinding block 100 is mainly composed of a corrugated metal part 1 and a resin part 2 cast around the metal part.
[0042] The metal part is prepared from the following components in parts by weight: 10-30 parts of foamed copper powder, 3-10 parts of foamed nickel powder, 5-15 parts of diamond, 20-40 parts of iron-copper alloy powder, 5-10 parts of phosphorus iron powder, 15-30 parts of carbonyl iron powder, and 1-5 parts of phosphorus powder.
[0043] The resin component is prepared from abrasive powder, unsaturated resin liquid, cobalt solution, methyl ethyl ketone peroxide, diluent, and coupling agent. The weight ratio of abrasive powder to unsaturated resin liquid is 1:(0.7-1.2). The amount of cobalt solution added is 1-2% of the weight of the unsaturated resin liquid, the amount of methyl ethyl ketone peroxide added is 2-4% of the weight of the unsaturated resin liquid, the amount of diluent added is 1-3% of the weight of the unsaturated resin liquid, and the amount of coupling agent added is 3-5% of the weight of the unsaturated resin liquid. The abrasive powder is prepared from the following components in parts by weight: 5-15 parts nylon powder, 5-15 parts zinc oxide, 5-15 parts copper foam powder, 10-20 parts black silicon carbide, 5-15 parts alumina, 1-5 parts calcium carbonate, and 5-15 parts diamond.
[0044] As a further embodiment, in the metal portion, the porosity of the foamed copper powder is 50-81% and the average pore size is 0.2-4 mm.
[0045] The porosity of the foamed nickel powder is 50-98%, and the average pore size is 0.1-2 mm;
[0046] The diamond has a particle size of 0.08-0.16 mm, the iron-copper alloy powder has a particle size of 300-500 mesh, the phosphorus iron powder has a particle size of 800-1200 mesh, the carbonyl iron powder has a particle size of 300-500 mesh, and the phosphorus powder has a particle size of 300-500 mesh.
[0047] As a further embodiment, in the resin portion, the unsaturated resin liquid is selected from unsaturated polyester resin of grade 196 provided by Shin Yang Technology Co., Ltd. Compared to powdered epoxy resin or phenolic resin, unsaturated resin is inexpensive, saving costs and has a faster curing time. Compared to other grades of unsaturated resin such as 191, the grinding blocks have better toughness and are more suitable for the coarse grinding process of this invention.
[0048] The diluent is selected from styrene, acetone, toluene, and butanol; the coupling agent is selected from silane coupling agents, titanate coupling agents, and aluminate coupling agents.
[0049] The porosity of the foamed copper powder is 50-81%, and the average pore size is 0.2-4 mm.
[0050] The nylon powder has a particle size of 300-500 mesh, the zinc oxide has a particle size of 300-500 mesh, the black silicon carbide has a particle size of 150-300 mesh, the alumina has a particle size of 300-500 mesh, the calcium carbonate has a particle size of 300-500 mesh, and the diamond has a particle size of 0.08-0.16 mm.
[0051] This invention also provides a method for preparing a metal-resin bonded grinding block for the rough grinding process of large ceramic slabs, comprising the following steps:
[0052] (1) Fabrication of the wavy metal parts
[0053] The metal part is prepared according to the following components by weight: 10-30 parts of foamed copper powder, 3-10 parts of foamed nickel powder, 5-15 parts of diamond, 20-40 parts of iron-copper alloy powder, 5-10 parts of phosphorus iron powder, 15-30 parts of carbonyl iron powder, and 1-5 parts of phosphorus powder. The above components except diamond are mixed in a three-dimensional mixer for 30-50 minutes. Then, the amount of diamond in the formula and 1.5%-3% of liquid paraffin by weight of the powder are added and mixed again for 50-60 minutes. The mixed powder is poured into a graphite mold and pressed into shape using a hot press. After pressing, the surface is polished to remove burrs and obtain a wavy metal part. As a further preferred option, in step (1), the pressing conditions are as follows: the hot press is heated from an initial temperature of 100°C and 20KN to 750°C and 100KN in stages, and held for 2-4 minutes.
[0054] (2) Preparation of resin abrasive fluid
[0055] The abrasive powder is formulated according to the following components by weight: 5-15 parts nylon powder, 5-15 parts zinc oxide, 5-15 parts copper foam powder, 10-20 parts black silicon carbide, 5-15 parts alumina, 1-5 parts calcium carbonate, and 5-15 parts diamond. The abrasive powder is then passed through a 46# sieve and dried in an oven to remove moisture. The dried powder is then poured into a three-dimensional mixer for mixing for 1-2 hours. The resulting abrasive powder is then ready for use.
[0056] Add the prescribed amount of unsaturated resin liquid to the mixing tank, add diluent at a rate of 1-3% of the weight of the unsaturated resin liquid; then add the well-mixed abrasive powder, the weight ratio of the abrasive powder to the unsaturated resin liquid being 1:(0.7-1.2), and stir evenly; add silane coupling agent at a rate of 3-5% of the weight of the unsaturated resin liquid, and stir evenly; add cobalt water at a rate of 1-2% of the weight of the unsaturated resin liquid, and stir evenly; then add methyl ethyl ketone peroxide at a rate of 2-4% of the weight of the unsaturated resin liquid, and stir evenly to obtain the resin abrasive liquid; in step (2), the temperature of the oven is set to 55-65℃ and kept at that temperature for 0.5-1 hour;
[0057] It is particularly important to note that in the production of coarse grinding blocks, when using unsaturated resin, the cobalt solution must be added and stirred thoroughly before adding methyl ethyl ketone peroxide; otherwise, an explosion may occur.
[0058] (3) Combination of metal and resin parts
[0059] Place the mold into the mold groove, place the corrugated metal part obtained in step (1) into the mold, pour the mixed resin abrasive liquid in step (2) into the mold, place the rubber pad on top of the mold so that the resin liquid and the rubber pad come into contact, then apply pressure to the rubber pad, turn on the ultrasonic device and the heating device, set the ultrasonic frequency to 35-45kHz, the ultrasonic time to 0.5-1 hour, the heating temperature of the heating device to 50-80℃, and the pressing time to 1-3 hours, perform ultrasonic and hot pressing curing, and take it out after complete curing. It can be used for the metal resin bonded abrasive block for the rough grinding process of ceramic slabs.
[0060] The adhesive pad is an accessory that connects the abrasive block to the mounting position on the polishing machine. In existing technologies, the processed abrasive block needs to be fixed to the adhesive pad by adhesive bonding or by attaching Velcro, facilitating the subsequent mounting of the module on the polishing machine. In this process, after the metal resin-bonded abrasive block has cured, there is no need for a separate adhesive pad attachment process and / or Velcro application. The abrasive block adheres to the adhesive pad during the curing of the poured resin, simplifying the processing and reducing costs.
[0061] The following are specific embodiments of the present invention. Unless otherwise specified, the raw materials, equipment and other materials used in the following embodiments can be obtained by purchasing.
[0062] Examples 1-3 and Comparative Examples 1-13
[0063] Weigh the raw materials according to the proportions in Table 1, and prepare metal-resin bonded grinding blocks according to the preparation methods in Table 1. This yields metal-resin bonded grinding blocks for different embodiments, as detailed in Table 1.
[0064] Table 1. Raw material ratio table for Examples 1-3
[0065]
[0066]
[0067]
[0068] In Table 1, the porosity of the copper foam powder is 50-81%, and the average pore size is 0.2-4 mm. The porosity of the nickel foam powder is 50-98%, and the average pore size is 0.1-2 mm. The particle size of the diamond is 0.08-0.16 mm, the particle size of the iron-copper alloy powder is 500 mesh, the particle size of the phosphorus iron powder is 1000 mesh, the particle size of the carbonyl iron powder is 400 mesh, and the particle size of the phosphorus powder is 500 mesh.
[0069] The resin component contains nylon powder with a particle size of 400 mesh, zinc oxide with a particle size of 500 mesh, black silicon carbide with a particle size of 300 mesh, alumina with a particle size of 400 mesh, calcium carbonate with a particle size of 500 mesh, and diamond with a particle size of 0.08-0.16 mm; the copper foam powder has a porosity of 50-81% and an average pore size of 0.2-4 mm; the unsaturated resin liquid is selected from unsaturated polyester resin of grade 196 provided by Xinyang Technology Co., Ltd.; the diluent is selected from styrene; and the coupling agent is selected from silane coupling agent.
[0070] Comparative Example 1
[0071] Compared with Example 2, the difference in Comparative Example 1 is that in the metal part formulation, conventional copper powder and nickel powder are used instead of foamed copper powder and foamed nickel powder, while the remaining amounts and processing conditions are the same as in Example 2.
[0072] Comparative Example 2
[0073] Compared with Example 2, the difference in Comparative Example 2 is that in the metal part formulation, a single foamed copper powder is used, with an amount of 26 parts, while the remaining amounts and processing conditions are the same as in Example 2.
[0074] Comparative Example 3
[0075] Compared with Example 2, the difference in Comparative Example 3 is that in the metal part formulation, a single foamed nickel powder is used, with an amount of 26 parts, while the remaining amounts and processing conditions are the same as in Example 2.
[0076] Comparative Example 4
[0077] Compared with Example 2, the difference in Comparative Example 4 is that the amount of nickel foam powder used in the metal part formulation is 20 parts, while the other amounts and processing conditions are the same as in Example 2.
[0078] Comparative Example 5
[0079] Compared with Example 2, the difference in Comparative Example 5 is that in the metal part of the formulation, conventional iron powder is used instead of carbonyl iron powder, while the other amounts and processing conditions are the same as in Example 2.
[0080] Comparative Example 6
[0081] Compared with Example 2, the difference in Comparative Example 6 is that in the metal part formulation, the amount of ferrophosphorus powder and phosphorus powder is 0 parts, while the other amounts and processing conditions are the same as in Example 2.
[0082] Comparative Example 7
[0083] Compared with Example 2, the difference in Comparative Example 7 is that the amount of phosphorus powder used in the metal part of the formula is 0 parts, while the other amounts and processing conditions are the same as in Example 2.
[0084] Comparative Example 8
[0085] Compared with Example 2, the difference in Comparative Example 8 is that in the resin formulation, powdered phenolic resin replaces unsaturated resin liquid, while the remaining amounts and processing conditions are the same as in Example 2.
[0086] Comparative Example 9
[0087] Compared with Example 2, the difference in Comparative Example 9 is that the amount of zinc oxide used in the resin formulation is 20 parts, while the remaining amounts and processing conditions are the same as in Example 2.
[0088] Comparative Example 10
[0089] Compared with Example 2, the difference in Comparative Example 10 is that the amount of nylon powder used in the resin formulation is 0 parts, while the other amounts and processing conditions are the same as in Example 2.
[0090] Comparative Example 11
[0091] Compared with Example 2, the difference in Comparative Example 11 is that the amount of foamed copper powder in the resin formulation is 0 parts, while the other amounts and processing conditions are the same as in Example 2.
[0092] Comparative Example 12
[0093] Compared with Example 2, the difference in Comparative Example 12 is that in the preparation method of the metal resin bonded grinding block, step (3) does not add the ultrasonic curing process, but directly hot presses the molding, that is, the ultrasonic frequency and ultrasonic time are both 0, and the remaining dosage and processing conditions are the same as in Example 2.
[0094] Comparative Example 13
[0095] Comparative Example 13 is a conventional resin-bonded grinding block with the following formula: 40 parts phenolic resin, 12 parts zinc oxide, 12 parts green silicon, 10 parts alumina, 8 parts glass fiber powder, 5 parts calcium carbonate, and 10 parts diamond.
[0096] The preparation methods of the metal-resin bonded grinding blocks in each example include the following steps:
[0097] (1) Fabrication of the wavy metal parts
[0098] The metal part is prepared according to the formula in Table 1; the components except diamond are mixed in a three-dimensional mixer for 40 minutes; then the amount of diamond and 2% of the weight of liquid paraffin are added, and the mixture is stirred again for 55 minutes; the mixed powder is poured into a pre-made graphite mold containing a corrugated cavity, and pressed into shape using a hot press. The pressing conditions are as follows: the hot press is initially heated to 100℃ and 20KN, then gradually increased to 750℃ and 100KN, and held for 3 minutes; after pressing, the surface is polished to remove burrs, resulting in the corrugated metal part.
[0099] (2) Preparation of resin abrasive fluid
[0100] The resin component was prepared according to the formula in Table 1. The nylon powder, zinc oxide, copper foam powder, black silicon carbide, alumina, calcium carbonate, and diamond were passed through a 46# sieve and then placed in an oven to dry in order to remove moisture from the powder. The oven temperature was set to 60℃ and kept at that temperature for 0.5 hours. The dried powder was then poured into a three-dimensional mixer for mixing for 1.5 hours. The powder was then removed and set aside to obtain abrasive powder.
[0101] Add unsaturated resin liquid and styrene diluent to the mixing tank; then add the mixed abrasive powder and stir evenly; add silane coupling agent and stir evenly; add cobalt water and stir evenly; then add methyl ethyl ketone peroxide and stir evenly to obtain resin abrasive liquid.
[0102] (3) Combination of metal and resin parts
[0103] Place the mold into the mold groove, place the corrugated metal part obtained in step (1) into the mold, pour the mixed resin abrasive liquid in step (2) into the mold, place the rubber pad on top of the mold so that the resin liquid and the rubber pad come into contact, then apply pressure to the rubber pad, turn on the ultrasonic device and the heating device, set the ultrasonic frequency of the ultrasonic device to 40kHz, the ultrasonic time to 0.5 hours, the heating temperature of the heating device to 60℃, and the pressing time to 2 hours, perform ultrasonic and hot pressing curing, and take it out after complete curing to obtain the metal resin bonded abrasive block.
[0104] Effect evaluation and performance testing
[0105] The performance of the grinding blocks of Examples 1-3 and Comparative Examples 1-13 was tested. The test items and results are shown in Table 2.
[0106] 1. Grinding block sharpness test
[0107] Sharpness was determined using vernier calipers by measuring the thickness change of the ceramic slab before and after processing, i.e., the depth of cut. The results are presented as slab thickness (mm). The greater the depth of cut, the sharper the abrasive block.
[0108] 2. Testing method for grinding block service life
[0109] Install the abrasive block on the polishing machine. During the polishing process, stop polishing when the ceramic surface reaches a polishing quality. Record the longest polishing time of the abrasive block, and record the results in hours (h).
[0110] 3. Polishing effect test
[0111] The grinding blocks from each example were installed on the 16 polishing heads of the coarse polishing machine. A large ceramic slab with dimensions of 3600mm×1600mm×15.5mm was polished under the same coarse polishing conditions. The surface of the ceramic slab was observed to see if it was flat and if there were any scratches. Flatness was observed under fluorescent light. The better the polishing effect, the smoother the light without bending.
[0112] Table 2 shows the performance test data of the grinding blocks for each example.
[0113]
[0114]
[0115] As shown in the table above and Figure 1-3As shown, compared to the conventional hot-pressed resin grinding blocks in Comparative Example 13, the grinding blocks used in the rough grinding process of this invention are metal-resin bonded grinding blocks made by combining hot-pressed strip metal with cast liquid resin. Replacing the existing hot-pressed resin grinding blocks with metal-resin bonded grinding blocks can improve the sharpness and service life of the grinding blocks, and also improve the polishing effect. The resulting ceramic slabs have no scratches on the surface, high flatness, and no bending of light under fluorescent lamps.
[0116] Compared with Example 2, the difference in the grinding block of Comparative Example 1 is that in the metal part of the formula, conventional copper powder and nickel powder are used instead of foamed copper powder and foamed nickel powder. The bonding strength between conventional copper powder and nickel powder and the other powders is reduced, which reduces the service life of the grinding block.
[0117] Compared with Example 2, the difference in the grinding blocks of Comparative Examples 2-3 lies in the use of single foamed copper powder or single foamed nickel powder in the metal part formulation. This shows that although single foamed copper powder or nickel powder improves the sharpness / wear resistance of the grinding block, its effect is still not as good as the combination of the two to strengthen the matrix and increase toughness, sharpness and wear resistance.
[0118] Compared with Example 2, the difference in the grinding block of Comparative Example 4 is that the amount of foamed nickel powder in the metal part of the formulation is too large, indicating that too much foamed nickel powder actually reduces the sharpness of the grinding block.
[0119] Compared with Example 2, the difference in the grinding block of Comparative Example 5 is that conventional iron powder is used instead of carbonyl iron powder in the metal part of the formulation, which shows that carbonyl iron powder is beneficial to improving the wear resistance of the grinding block.
[0120] Compared with Example 2, the difference in the grinding block of Comparative Example 6 is that the amount of ferrophosphorus powder and phosphorus powder in the metal part formula is 0 parts, which shows that ferrophosphorus powder and phosphorus powder can improve the sharpness of the grinding block.
[0121] Compared with Example 2, the difference in the grinding block of Comparative Example 7 is that the amount of phosphorus powder in the metal part of the formula is 0 parts, which indicates that phosphorus powder has a greater effect on improving the sharpness of the grinding block.
[0122] Compared with Example 2, the difference in the grinding block of Comparative Example 8 is that in the resin formulation, powdered phenolic resin replaces unsaturated resin liquid, indicating that when using foam metal, the liquid resin flows more completely in the pores of the foam metal, significantly improving the bonding ability with the metal part, thereby improving its service life.
[0123] Compared with Example 2, the difference in the grinding block of Comparative Example 9 is that the amount of zinc oxide in the resin formulation is too large, which makes the unsaturated resin liquid viscous, easily causing uneven mixing, which is not conducive to bonding with the metal part and reduces the service life of the grinding block.
[0124] Compared with Example 2, the difference in the grinding block of Comparative Example 10 is that the amount of nylon powder in the resin part of the formulation is 0 parts, which indicates that nylon powder is beneficial to improving the wear resistance of the grinding block.
[0125] Compared with Example 2, the difference in the grinding block of Comparative Example 11 is that the amount of foamed copper powder in the resin formulation is 0 parts, which indicates that the foamed copper powder can make the resin liquid and powder bond stronger, less prone to tooth decay, and also improve service life.
[0126] Compared with Example 2, the difference of the grinding block in Comparative Example 12 is that in the preparation method of the metal-resin bonded grinding block, step (3) does not add the ultrasonic curing process, but directly hot-presses the molding process. This shows that the ultrasonic combined with hot pressing method makes the liquid flow more uniform, which can promote the curing effect and the bonding ability between metal and resin, and improve the service life and grinding effect of the grinding block.
[0127] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing metal-resin bonded grinding blocks for the rough grinding process of large ceramic slabs, characterized in that, Includes the following steps: (1) Fabrication of the wavy metal parts The metal component is prepared according to the following weight proportions: 10-30 parts of foamed copper powder, 3-10 parts of foamed nickel powder, 5-15 parts of diamond, 20-40 parts of iron-copper alloy powder, 5-10 parts of phosphorus iron powder, 15-30 parts of carbonyl iron powder, and 1-5 parts of phosphorus powder. All components of the metal component except for diamond are mixed using a three-dimensional mixer for 30-50 minutes. Then, the amount of diamond and 1.5%-3% of liquid paraffin by weight of the powder are added, and the mixture is stirred again for 50-60 minutes. The mixed powder is poured into a graphite mold and pressed into shape using a hot press. After pressing, the surface is polished to remove burrs, resulting in a wavy metal component. (2) Preparation of resin abrasive fluid The abrasive powder is formulated according to the following components by weight: 5-15 parts nylon powder, 5-15 parts zinc oxide, 5-15 parts copper foam powder, 10-20 parts black silicon carbide, 5-15 parts alumina, 1-5 parts calcium carbonate, and 5-15 parts diamond. The abrasive powder is then passed through a 46# sieve and dried in an oven to remove moisture. The dried powder is then poured into a three-dimensional mixer for mixing for 1-2 hours. The resulting abrasive powder is then ready for use. Add the prescribed amount of unsaturated resin liquid to the mixing tank, add diluent, the amount of which is 1-3% of the weight of the unsaturated resin liquid; then add the well-mixed abrasive powder, the weight ratio of the abrasive powder to the unsaturated resin liquid is 1:(0.7-1.2), and stir evenly; add silane coupling agent, the amount of which is 3-5% of the weight of the unsaturated resin liquid, and stir evenly; add cobalt water, the amount of which is 1-2% of the weight of the unsaturated resin liquid, and stir evenly; then add methyl ethyl ketone peroxide, the amount of which is 2-4% of the weight of the unsaturated resin liquid, and stir evenly to obtain resin abrasive liquid; in step (2), the temperature of the oven is set to 55-65℃ and kept warm for 0.5-1 hour; (3) Combination of metal and resin parts Place the mold into the mold slot, place the corrugated metal part obtained in step (1) into the mold, pour the mixed resin abrasive liquid in step (2) into the mold, place the rubber pad on top of the mold so that the resin liquid and the rubber pad come into contact, then apply pressure to the rubber pad, turn on the ultrasonic device and the heating device, and perform ultrasonic and hot pressing curing. Set the ultrasonic frequency to 35-45kHz, the ultrasonic time to 0.5-1 hour, the heating temperature of the heating device to 50-80℃, and the pressing time to 1-3 hours. After complete curing, take it out to obtain the metal resin bonded abrasive block for the rough grinding process of ceramic slabs.
2. The method for preparing metal-resin bonded grinding blocks for the rough grinding process of large ceramic slabs as described in claim 1, characterized in that, In the metal portion, the porosity of the foamed copper powder is 50-81%, and the average pore size is 0.2-4 mm.
3. The method for preparing metal-resin bonded grinding blocks for the rough grinding process of large ceramic slabs as described in claim 1, characterized in that, In the metal portion, the porosity of the foamed nickel powder is 50-98%, and the average pore size is 0.1-2 mm.
4. The method for preparing metal-resin bonded grinding blocks for the rough grinding process of large ceramic slabs as described in claim 1, characterized in that, In the metal portion, the diamond has a particle size of 0.08-0.16 mm, the iron-copper alloy powder has a particle size of 300-500 mesh, the phosphorus iron powder has a particle size of 800-1200 mesh, the carbonyl iron powder has a particle size of 300-500 mesh, and the phosphorus powder has a particle size of 300-500 mesh.
5. The method for preparing metal-resin bonded grinding blocks for the rough grinding process of large ceramic slabs as described in claim 1, characterized in that, In the resin portion, the diluent is selected from styrene, acetone, toluene, and butanol; the coupling agent is selected from silane coupling agents, titanate coupling agents, and aluminate coupling agents.
6. The method for preparing metal-resin bonded grinding blocks for the rough grinding process of large ceramic slabs as described in claim 1, characterized in that, In the resin portion, the porosity of the foamed copper powder is 50-81%, and the average pore size is 0.2-4 mm.
7. The method for preparing metal-resin bonded grinding blocks for the rough grinding process of large ceramic slabs as described in claim 1, characterized in that, In the resin component, the nylon powder has a particle size of 300-500 mesh, the zinc oxide has a particle size of 300-500 mesh, the black silicon carbide has a particle size of 150-300 mesh, the alumina has a particle size of 300-500 mesh, the calcium carbonate has a particle size of 300-500 mesh, and the diamond has a particle size of 0.08-0.16 mm.
8. The method for preparing metal-resin bonded grinding blocks for the rough grinding process of large ceramic slabs as described in claim 1, characterized in that, In step (1), the pressing conditions are as follows: the hot press is heated in stages from an initial temperature of 100°C and 20KN to 750°C and 100KN, and held for 2-4 minutes.
Citation Information
Patent Citations
Manufacturing method for diamond and resin combined grinding block and diamond and resin combined grinding block
CN107322500A
Porous self-sharpening metal-based grinding wheel and preparing method thereof
CN110497324A